Slavery by another name [videorecording (DVD)] - Pollard, Sam; Pollard, Sam; Fishburne, Laurence, III, 1961-; Blackmon, Douglas A. (PBS Distribution, 2012)
Challenges one of America's most cherished assumptions, the belief that slavery in the U.S. ended with Abraham Lincoln's Emancipation Proclamation, by telling the harrowing story of how, in the South, a new system of involuntary servitude took its place with shocking force.